Plasma Engine for Aircraft - Chua, Daniel Chong Jing (2018)
This final year project titled as “Plasma Engine for Aircraft”. The main objective of this project is to create a green energy for the aircraft’s engines. Plasma is the fourth state of matter in the universe. It is a green energy and new technology which is widely used in the spacecraft’s engine and surface treatment application. A plasma can be formed by adding sufficient heat to the gas and it is a hot ionized gas which has its unique properties. In fact, an aircraft operates in the sky and the engines release pollutants such as carbon dioxide, nitrous oxides, sulphate, and soot from the exhausts. All these pollutants are very harmful to the environment and the ecosystems, therefore the plasma engine is created and designed to solve these problems and reduce the consumption of fuels. However, this project is mainly focusing on the mechanical, chemical and environmental engineering fields. As the working concept of the turbine engine is purely based on the mechanical part while the chemical part covers the concept of plasma energy. In order to successfully develop and build the plasma engines for the aircrafts, a lot of investigations and researches must be done and executed.